Psychiatric Comorbidity in Neurological Disorders: Towards a Multidisciplinary Approach to Illness Management in the United Arab Emirates - Alsaadi, Taoufik; Kassie, Seada; Mohamed Ali, Ola; Mozahem, Khaldoun; al Fardan, Safana; Ahmed, Ahmed M. (Frontiers in Psychiatry, 2019)
Abstract Aim: to determine the prevalence of mood and anxiety disorders in undiagnosed patients attending neurological services, and detect rates of referral to and attendance of psychiatric services Methods: Depressive symptoms and anxiety were assessed in 395 adult patients with primary diagnoses of neurological disorders. The Patient Health Questionnaire nine-item (PHQ-9) depression scale, and Generalized Anxiety Disorder seven-item (GAD-7) scale were administered. Demographic details of the patients were recorded. Referral to and attendance of psychiatric services were recorded for patients scoring within the clinical range of depression and anxiety disorders (scores >10). Results: There was a 39% prevalence rate of depressive symptoms, 34% rate of anxiety, and 35.4% concurrent rate of both disorders in this cohort. The referral rate to psychiatric services was 33.6% and attendance rate was 47.8%. There was significant association between severity of psychiatric symptoms and referral to psychiatric services, as well as significant association between comorbid psychiatric symptoms and attendance to psychiatric services. Conclusion: Our results indicate similar prevalence rates of comorbid psychiatric symptoms to studies carried out in the Middle-east and North Africa (MENA) region and relatively high attendance and referral rates to psychiatric services. Implications: The results shed light on the clinical profile of patients in this region and support the need for integrated collaborative medical services. Moreover, findings have important implications on health care policies pertaining to resource distribution and funding.